Why Do Responses to Age‐Based Marketing Stimuli Differ? The Influence of Retirees' Group Identification and Changing Consumption Patterns. Issue 10 (October 2014) - Wolf, Friedemann; Sandner, Philipp; Welpe, Isabell M.
ABSTRACT This study analyzes how retired consumers respond to age‐based marketing stimuli using survey data from 236 retirees over the age of 60 years. Specifically, it investigates the factors that influence retirees' intentions to use senior discounts and intentions to accept exclusive offers for seniors (e.g., educational classes for seniors), as well as their evaluation of age‐related labels (e.g., "60+"). The results show that retirees who identify more strongly with other retirees and who generally change their consumption patterns following retirement are more likely to respond positively to age‐based marketing stimuli. Additionally, the data suggest that cognitive age negatively moderates the role of retirees' identification with other retirees in terms of their responses to age‐based marketing stimuli. However, the influence of these variables differs significantly across the types of stimuli considered. The findings help to explain ambiguities in previous studies that did not consider differences among mature consumers beyond age and age‐group membership or among the types of stimuli. The implications of these findings with respect to effective marketing to retired consumers are discussed.